PRIORITAS KAPABILITAS DINAMIS VS OPERASIONAL ATAS KINERJA PERUSAHAAN DENGAN GREY-AHP - Didit Damur Rochman; Annisa Maharani (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
The operational capabilities of a company represent its routine and ordinary activities undertaken to sustain and generate performance. In the manufacturing sector, particularly in pharmaceuticals, there is a greater demand for higher operational capabilities compared to other manufacturing sectors due to the relevance to human health. The pivotal role of dynamic capabilities is purported to significantly impact the enhancement of operational capabilities, both directly and indirectly affecting company performance. This research proposal aims to investigate how dynamic capabilities influence company capabilities and performance, particularly in the pharmaceutical manufacturing industry in the Greater Bandung area. The study employs the Grey-Analytical Hierarchy Process (Grey-AHP) method to analyze the impact of dynamic capabilities (Sensing, Seizing, and Reconfiguring) on company performance in the pharmaceutical industry of the Greater Bandung area. Surveys were conducted among respondents from the pharmaceutical industry, revealing that, although dynamic capabilities received a lower ranking compared to operational capabilities, the integration of the Grey-AHP method provides profound insights into their relative influence. Findings indicate that a focus on operational capabilities, particularly through Standard Operating Procedures (SOP) and information systems, remains crucial, but dynamic capabilities should not be entirely disregarded to confront market uncertainties and ensure the sustainability of the dynamic pharmaceutical industry